Studies and Charge Transport Properites of 9-N-Allylcarbazole Homologous - RAMDAN, N.; HAOUAM, A.; GHEID, A. (Asian Journal of Chemistry, 2010)
Many reports are available in literature about the poly 9-N-carbazole derivatives concerning the synthesis and photoconductivity. The photoconductivity of this series of polymers has been taken a great part in many applied techniques, especially in the domain of electronics, photovoltaic effect and electro-photography. Poly allyl carbazole derivatives as donor of electrons were synthesized and the molecular orbital charges were calculated. The polymer homologous will be complexed with some electron acceptors by mixing or grafting on other macromolecules and deposited on solid surfaces as thin layers.